UNJUK KERJA REAKTOR ANAEROB LEKAT DIAM TERENDAM DENGAN MEDIA PENYANGGA POTONGAN BAMBU - Indriyati, Indriyati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Fixed Bed Anaerobic reactor that use support material from bamboo ings can be used as waste water biological treatment without oxygen inside reactor. On the experiment that use soybean sauce waste waterwith high organic content.According to the experiment, the optimum performance result was 3.5 days withloading rate 0.71 kg COD/m3.day and bamboo rengs can be used as supportmaterial.